2021
DOI: 10.1002/cm.21678
|View full text |Cite
|
Sign up to set email alerts
|

Measuring force generation within reconstituted microtubule bundle assemblies using optical tweezers

Abstract: Kinesins and microtubule associated proteins (MAPs) are critical to sustain life, facilitating cargo transport, cell division, and motility. To interrogate the mechanistic underpinnings of their function, these microtubule‐based motors and proteins have been studied extensively at the single molecule level. However, a long‐standing issue in the single molecule biophysics field has been how to investigate motors and associated proteins within a physiologically relevant environment in vitro. While the one motor/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…The cytoskeleton consists of elements such as filaments, crosslinkers, and motor proteins that have vastly different mechanical, motile, and force generating capabilities yet work concertedly to perform large-scale tasks, such as cell division and translocation. 1,2 In many cases, when the cytoskeleton is studied in vitro , investigators are considering one family of the cytoskeleton at a time (e.g. actin and myosin or microtubules and kinesin) and are often working close to the single molecule level.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…The cytoskeleton consists of elements such as filaments, crosslinkers, and motor proteins that have vastly different mechanical, motile, and force generating capabilities yet work concertedly to perform large-scale tasks, such as cell division and translocation. 1,2 In many cases, when the cytoskeleton is studied in vitro , investigators are considering one family of the cytoskeleton at a time (e.g. actin and myosin or microtubules and kinesin) and are often working close to the single molecule level.…”
Section: Figurementioning
confidence: 99%
“…2,3 While single molecule studies have revealed invaluable information about motor protein properties such as processivity, stepping, and force generation capability, studies are increasingly finding that new behaviors emerge when motors, proteins, and filaments begin working together in groups that are not the sum of the constituent single molecule properties. 1,2,4 The design principles behind these emergent cytoskeletal mechanics are not yet understood but will be necessary for understanding the basic rules of life, as well as applications like building synthetic cells, deciphering mechanisms of cytoskeletalbased diseases, and engineering smart materials. [4][5][6][7][8] Actomyosin emergent mechanics are especially interesting as myosin II behavior is strikingly different between the single molecule level and when in ensembles.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Efficient cargo transports in cells are performed by motor proteins such as kinesin motors [1][2][3][4][5][6]. Nonmotor microtubule-associated proteins (MAPs) are also involved in intracellular transports [6][7][8][9][10][11][12][13][14]. Kinesin motors can move directionally along microtubule (MT) filaments towards the plus end by the hydrolysis of ATP [3][4][5].…”
Section: Introductionmentioning
confidence: 99%